How Do Halal Labels, Pricing, and Promotion Affect Sasha Toothpaste Purchasing Decisions? - Sekar Alma Arifitria; Reny Fitriana Kaban; Hidajat Sofyan Widjaja (Perbanas Institute, 2023)
During the pandemic, many companies experienced decline in revenue, including the toothpaste industry. Sasha toothpaste product is one of the halal toothpaste brands that has variability so authors conducted research on several variables that can influence purchasing decisions related to sales of Sasha toothpaste. The purpose of this study was to determine and analyze the effect of the Halal label, price, and promotion on purchasing decisions for Sasha toothpaste. Descriptive analysis with quantitative approach is used in the research design. With 75 respondents and non-probability sampling technique, it is continued with several analytical test. The results of this study indicate that the Halal label has no effect on the decision to buy Sasha toothpaste while the price and promotion do. At the simultant way, halal label, price and promotion affect decision to buy Sasha toothpaste. The halal label variable in making a consumer decision to buy toothpaste is a novelty in this study, because previous research focused more on marketing mix variables such as price and promotion only. It is recommended that the placement of halal label on this product be emphasized more clearly so consumers can be more aware of the existence of halal label on its packaging